Optimization of Control of a Flexible Manufacturing Line - Bartkevičius, S.; Daunoras, J.; Šarkauskas, K. (Elektronika ir Elektrotechnika, 2005)
Optimal and adaptive control of a flexible manufacturing line served by robots and manipulators causes the appearance of asynchronous processes. The carried out analysis showed that control according to priorities loses its effectiveness because of the failure of synhronization. Desiring to use production capacities optimally, it is necessary to change the algorithms of interruption service. This became obvious after the carried out simulation. To attend system with asynchronous processes effectively, it is necessary to use algorithms of interruption service analyzing situations and the assuming solution what operation must be carried out: to continue the performed operation or to recall it and to carry out new, returning recalled into general queue or unconditionally to carry out after the fulfillment of operation, which replaced it. Ill. 9, bibl. 11 (in Lithuanian; summaries in Lithuanian, English and Russian).